МУСА БИГИЕВ: ЖИЗНЬ И ИДЕЯ РЕФОРМЫ ОБРАЗОВАНИЯ = MUSA BIGIEV (1875-1949): Life and ideas to reform education - Akhmetova, Elmira (Kazan Federal University, 2016)
This short paper discusses the emphasis of Musa Bigiev on the importance of reforming the educational system. The first two parts of the paper highlights the life of the scholar in line with his learning experiences throughout the Muslim word to demonstrate the reasons for his call for educational reforms. As paper suggests, throughout his scholarly life, Bigiev emphasized on the role of education in forming individuals and reforming the Muslim society. The last part of the paper discusses the solutions of Bigiev to change the situation in education.